Pengembangan Media Puzzle Berseri untuk Membantu Meningkatkan Kemampuan Menggosok Gigi pada Anak Autis Kelas Dasar - Narulita, Reita; Jaya, Indra; Taboer, Mohammad Arif (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This innovative work research aims to develop a learning media in the form of serial puzzle media that can help children with autism to improve the ability of brushing teeth. Researchers developed serial puzzle media because they needed a learning media for self-development in brushing teeth of basic class autistic children. This media development uses the Research and Development (RnD) method with the PPE development model consisting of three stages, including the stages of planning, production, and evaluation.The data collection technique was carried out through validation by three experts with different instruments, namely media experts, material experts and autism children experts.This serial puzzle media gets the overall average result that has been achieved is good, with score of 56% according to media experts, 92,85% according to material experts, and 92,85 according to autism experts out of 100%. The average value obtained, it can be concluded that this serial puzzle media is declared feasible and can be used to help children with autism in developing self-brushing teeth. It is hoped that teachers and parents can use serial puzzle media in teaching self-development for brushing their teeth.